منهج أبي المعالي الجويني في نقد الكتاب المقدس من خلال كتابه - دكار, الياس (جامعة الوادي - University of Eloued, 2019)
Judaism and Christianity before the advent of Islam were subjected to great distortion, where it was the scene of chaos and absurdity by its men. There is nothing left of them but a little uniformity, there is only a little left of Tawheed, and when Islam came showed that these books have been subjected to distortion and increase or decrease or switch, and that the Koran is the only book that has not been distorted, so Muslims have since the time of the Prophet - peace be upon him - to this day by calling for the correct way and correct method, which is Islam, spread widely, but the enemies of Islam did not satisfy them this large and global spread of Islam, they conducted fierce campaigns against him, , And that Islam is nothing but hieroglyphs, so Muslims turned to respond to such suspicions, and wrote books and letters in a statement to negate the doctrines of other boredom, and the deviation of their books, especially the books of Judaism and Christianity, represented in the Bible and the Bible. Among these scholars was: The Imam of the Two Holy Mosques; Abi Maali AlJuwaini in his book: ” The healing of the exalted in the statement of what occurred the Torah and the Gospel of the switch”.
شفاء الغليل في بيان ما وقع في التوراة والإنجيل من التبديل
مقال
Keywords: اليهودية؛ النصرانية؛ الجويني؛ شفاء الغليل